The Influenced of Laboratory Equipment Utilization towards Students Learning Activities and Concept Mastery on Structure and Function of Plants Tissues Subject Matter - Ajeng Pratiwi; Darlen Sikumbang; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Based on observation and interview with biology teacher in SMP N 4 Gedongtataan, students learning activities and concept mastery were not optimally developed yet. An alternative that can be used to improve learning activities and concept mastery is using laboratory equipment. This study aims to understand the influence of laboratory equipment utilization towards student activities and concept mastery. This study is quasi experiment using pretest posttest group non equivalent design. Sample in this experiment are students from VIII C and VIII D which obtained from population by cluster random sampling method. Quantitative data obtained from average of pretest and posttest scores which statistically analyzed with U-test using SPSS version 17 in 95% confidence levels. Qualitative data are student’s concept mastery, learning activities and students responses about laboratory equipment utilization which descriptively analyzed. Result of this study shown that the average of students concept mastery in experimental class are higher than control (experiment= 65.81; control = 29.1). The average of student learning activities percentage in all observed aspects in experimental class shown higher enhancement than control (experiment = 79.9; control = 72.21) most of the students also gives positive responses to laboratory equipment utilization.  Key words: structure and function of plants tissues, laboratory equipment media